Metacognition Skill Exploration in Six Developing Countries: A Systematic Literature Review Towards Advancing Learning Quality - Puteri, Anisa; Ardianto, Didit (Universitas Negeri Semarang, 2023)
This study was conducted to analyze the literature related to the role ofmetacognition in science learning in six developing countries in an effort toimprove the quality of learning. The objectives of this study include: 1) toexplore the role of metacognition as a learning strategy applied to sciencelearning; 2) to explore the role of students' metacognition skills in sciencelearning. 3) knowing the role of metacognition in science learning to improvethe quality of science learning. The benefit of this research is to facilitateresearchers in obtaining literature that is suitable for analysis related to theresearch title to be carried out by researchers. The method of this research is touse the Systematic Literature Review (SLR) method, which consists of 4 steps,including identification, screening, eligibility, and inclusion. The results of thisstudy are obtained from as much as six pieces of literature that are suitable foranalysis. The results of the analysis of this article include: 1) Some parts of thecountry applying metacognition strategies in science learning are proven to beable to improve 21st century skills and also concept understanding. 2) Someparts of the country apply several innovative learning models that are able toimprove students' metacognition skills. The level of education that is widelyused in the research studies reviewed is 40% at the junior and senior high schoollevel and 20% at the university level. It is expected that this research willemphasize common patterns, challenges, and opportunities in using metacognitions skills in various science education contexts by gathering informationfrom various relevant studies.